Green marketing strategy increases the effect of green knowledge on green purchase intention - Yunita Hasnah Devina; Roni Kastaman; Efri Mardawati (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
The main objective of this study was to determine the effect of green marketing as a mediating variable on increasing green knowledge variables on increasing consumer buying interest in eco-friendly products. Questionnaires were distributed to 110 Starbucks Coffee consumers in Bandung, which were analyzed by descriptive analysis to describe general characteristics of the respondents. The Structured Equation Model – Partial Least Square (SEM-PLS) analysis was also used to confirm the theory that there is an influence of green marketing variables as a mediating variable on increasing green knowledge on consumer buying interest in green products. The results showed that consumers of Starbucks Coffee in Bandung were dominated by women in their early adulthood who worked as private employees with moderate income. The implementation of the green marketing strategy by Starbucks is expected to maximize customer service in accordance with the description of consumer characteristics with the green marketing strategy implemented by Starbucks Coffee. The provision of green knowledge that affects the increase in consumer purchase intention of green products can be further improved positively and significantly through the application of green marketing strategies as a mediating variable.